Eyes of the void eaudiobook - Tchaikovsky, Adrian (The Final Architecture, 2022)
The Arthur C. Clarke award-winning author of Children of Time brings us the second novel in an extraordinary space opera trilogy about humanity on the brink of extinction, and how one man's discovery will save or destroy us all. After eighty years of fragile peace, the Architects are back, wreaking havoc as they consume entire planets. In the past, Originator artefacts – vestiges of a long-vanished civilization – could save a world from annihilation. This time, the Architects have discovered a way to circumvent these protective relics. Suddenly, no planet is safe. Facing impending extinction, the Human Colonies are in turmoil. While some believe a unified front is the only way to stop the Architects, others insist humanity should fight alone. And there are those who would seek to benefit from the fractured politics of war – even as the Architects loom ever closer. Idris, who has spent decades running from the horrors of his past, finds himself thrust back onto the battlefront. As an Intermediary, he could be one of the few to turn the tide of war. With a handful of allies, he searches for a weapon that could push back the Architects and save the galaxy. But to do so, he must return to the nightmarish unspace, where his mind was broken and remade. What Idris discovers there will change everything.